Trauma processing therapy: An integrated psychotherapy approach to process traumatic memories - Ardian, Jiemi; Ismaya, Matius D. R. D.; Octaviani, Ines D.; Deazara, Kania (Edelweiss Applied Science and Technology, 2025)
Trauma profoundly affects emotional well-being, cognitive functioning, behavior, and physical health, often leading to enduring psychological distress. While conventional therapies such as Cognitive Behavioral Therapy (CBT) and psychodynamic therapy offer partial relief, they frequently fall short in addressing the deep-seated emotional and physiological impacts of trauma. Emerging modalities like mindfulness, hypnosis, and ego-state therapy show potential in tackling these multifaceted effects but often require extensive time due to the gradual nature of memory reprocessing and emotional resolution, which can pose significant barriers for clients. This paper introduces Trauma Processing Therapy (TPT), an integrated approach that combines principles from mindfulness, hypnoanalysis, and ego-state therapy. TPT focuses on processing traumatic memories, emphasizing that these memories contain ego states burdened by unresolved issues, unspoken voices, and unmet needs. By acknowledging and addressing these needs, TPT facilitates the processing of traumatic memories, enabling profound psychological resolution. Unlike traditional trauma therapies that often require extended treatment durations, TPT leverages dissociative phenomena to access and process traumatic memories efficiently and effectively. This approach maintains both safety and efficacy. Case studies of clients treated with TPT are presented, demonstrating its potential effectiveness and highlighting its value as an innovative advancement in trauma therapy.